Social stigma in leprosy - Marahatta, S; Ghimire, A; Jha, N; Pokhrel, S M; Rayamajhi, S; Jirel, S (Journal of Chitwan Medical College, 2015)
Leprosy, an infectious disease, is a highly stigmatized disease. It directly affects patients’ physical, psychological, social and economical well-being. To know the stigma faced by the patients in the family and community. The study was carried out at Netherlands Leprosy Relief, Biratnagar, Nepal. Verbal consent was taken from each patient. A total number of 34 patients who were diagnosed to have leprosy were interviewed. Data were collected using structured interview schedule that included questions seeking information about all aspects of objective. Although both men and women faced the social stigma of the disease, women suffered more rejection by the family members (50%), neighborhood (75%) and work places (62.5%) in comparison to male patients, who are affected maximum at work places (39%) and minimum in family (7.69%). Illiterate were avoided by family members (25%) and co-workers (75%) whereas literate were not. All unemployed patients were neglected in community whereas only 21.42% of employed were neglected. Leprosy is a highly stigmatized disease. Patients are neglected by their family and society. Therefore community education component of Leprosy Control Program needs to be strengthened.